Differences in protein expression, at the basal state and at 2 h of insulin infusion, in muscle biopsies from healthy Arab men with high or low insulin sensitivity measured by hyperinsulinemic euglycemic clamp - Bettahi, Ilham; Krishnankutty, Roopesh; Jaganjac, Morana; Suleiman, Noor Nabeel M.; Ramanjaneya, Manjunath; Jerobin, Jayakumar; Hassoun, Shaimaa; Alkasem, Meis; Abdelhakam, Ibrahem; Iskandarani, Ahmad; Samra, Tareq A.; Mohamed-Ali, Vidya; et al. (Frontiers in Endocrinology, 2023)
Background: Skeletal muscle is the main sites for insulin-dependent glucose disposal. The hyperinsulinemic euglycemic clamp (HIEC) is the gold standard for assessment of insulin sensitivity (IS). We have previously shown that insulin sensitivity, measured by HIEC, varied widely among a group of 60 young healthy men with normoglycemia. The aim of this study was to correlate the proteomic profile of skeletal muscles to insulin sensitivity. Methods: Muscle biopsies from 16 subjects having the highest (M>13; n=8, HIS) and least (M<6, n=8, LIS) IS, were obtained at baseline and during insulin infusion after stabilization of blood glucose level and glucose infusion rate at the end of the HIEC. Samples were processed for the quantitative proteomic analysis approach. Results: At baseline, 924 proteins were differentially expressed in HIS and LIS groups. Among 924 proteins detected in both groups, 3 were suppressed, and 3 were increased significantly in LIS compared to the HIS subjects. When comparing insulin-responsive genes between LIS and HIS, 835 proteins were detected in both groups after insulin stimulation. Among 835 proteins, 2 showed differential responsiveness to insulin; ATP5F1 protein was decreased, and MYLK2 was higher in the LIS group compared to the HIS group. Our data suggest that alteration in mitochondrial proteins and increased protein involved in fast-twitch fiber contribute to decreased insulin sensitivity. Conclusions: These results provide an understanding of the molecular mechanisms determining insulin sensitivity status in skeletal muscle and may represent early events for the development of insulin resistance, pre-diabetes, gestational diabetes, and type 2 diabetes.